Capaian Pembelajaran Seni Musik Pada Kurikulum Merdeka Sebagai Wujud Merdeka Belajar - Lanang Riyadi; Nandang Budiman (Program Studi Pendidikan Musik FBS UNP, 2023)
Purpose: Curriculum development in Indonesia has become a polemic with the existence of the Kurikulum Merdeka, which discusses learning outcomes that should be one of the answers to overcome learning objectives that have not been achieved in the previous curriculum. This article seeks to provide an overview of learning outcomes, especially in music subjects in the Kurikulum Merdeka, as a form of independent learning in schools, which is expected to be an understanding that educators can internalize about the importance of learning outcomes in music subjects. Method: The literature study is used in this research by collecting data through online media, articles, and books related to music learning outcomes in the Merdeka Curriculum in schools. Result and Discussion: This research describes the learning outcomes of music as a form of independent learning. The discussion reviewed includes learning outcomes, objectives, and characteristics of music learning in the Merdeka Curriculum. Music teaching in the Merdeka Curriculum is divided into phases A to F, and there are five elements included in music learning, including experiencing, reflecting, thinking and working artistically, creating, and impacting students and others. Music art subjects aim for students to be able to express, be sensitive, develop a sense of musicality, and be aware of their musicality.